2019
DOI: 10.1242/jcs.228684
|View full text |Cite
|
Sign up to set email alerts
|

GemC1 governs multiciliogenesis through direct interaction with and transcriptional regulation of p73

Abstract: A distinct combination of transcription factors elicits the acquisition of a specific fate and the initiation of a differentiation program. Multiciliated cells (MCCs) are a specialized type of epithelial cells that possess dozens of motile cilia on their apical surface. Defects in cilia function have been associated with ciliopathies that affect many organs, including brain and airway epithelium. Here we show that the geminin coiled-coil domain-containing protein 1 GemC1 (also known as Lynkeas) regulates the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…HeLa Kyoto and HEK293T cell lines were 2D cultured in Dulbecco's Modified Eagle Medium (DMEM, Gibco) supplemented with 10% fetal bovine serum (FBS, Gibco; Thermo Fisher Scientific, Inc.). Postnatal day 0 (P0) radial glial stem cells (pRGCs) were isolated from the mouse subventricular zone and 2D cultured in proliferation medium (PM) containing DMEM F12-Glutamax (Gibco; Thermo Fisher Scientific, Inc.), 10% (v/v) FBS, 1% (v/v) penicillin and streptomycin (P/S, Gibco; Thermo Fisher Scientific, Inc.), Epidermal Growth Factor (EGF, Peprotech) and Fibroblast Growth Factor (FGF, Peprotech) at a final concentration of 5µg/ml each, as previously described (Lalioti et al, 2019). Primary bone marrow-derived mesenchymal stem cells (MSCs) were isolated from the mouse femur, as described previously (Amend et al, 2016).…”
Section: Cell Lines and Primary Culturesmentioning
confidence: 99%
“…HeLa Kyoto and HEK293T cell lines were 2D cultured in Dulbecco's Modified Eagle Medium (DMEM, Gibco) supplemented with 10% fetal bovine serum (FBS, Gibco; Thermo Fisher Scientific, Inc.). Postnatal day 0 (P0) radial glial stem cells (pRGCs) were isolated from the mouse subventricular zone and 2D cultured in proliferation medium (PM) containing DMEM F12-Glutamax (Gibco; Thermo Fisher Scientific, Inc.), 10% (v/v) FBS, 1% (v/v) penicillin and streptomycin (P/S, Gibco; Thermo Fisher Scientific, Inc.), Epidermal Growth Factor (EGF, Peprotech) and Fibroblast Growth Factor (FGF, Peprotech) at a final concentration of 5µg/ml each, as previously described (Lalioti et al, 2019). Primary bone marrow-derived mesenchymal stem cells (MSCs) were isolated from the mouse femur, as described previously (Amend et al, 2016).…”
Section: Cell Lines and Primary Culturesmentioning
confidence: 99%
“…Previous studies reported that p73 was co-expressed with Foxj1 in basal cells of mice trachea, and was necessary for ependymal cell maturation, suggesting that p73 is needed for MCCs differentiation [ 28 , 36 ]. In p73 knockout mice, the FT showed defective ciliogenesis [ 28 , 30 , 37 ]. Thus, p73 and Ki67 have been shown to provide useful markers for identifying basal stem cells in FT.…”
Section: Discussionmentioning
confidence: 99%
“…As roof plate progenitors exit the cell cycle and commit to multiciliogenesis, TAp73 is turned on in multiciliated epithelial cells (Wildung et al 2019). Interestingly, both GEMC1 and MCIDAS were able to stimulate TAp73 expression (Lalioti et al 2019a). Gemc1 is expressed in differentiated epithelial cells, where its loss prevented activation of downstream targets including Mcidas , TAp73 and Foxj1 (Lalioti et al 2019a; Lewis and Stracker 2020).…”
Section: Discussionmentioning
confidence: 99%
“…GEMC1 and MCIDAS, complexed with cognate transcription partner E2Fs (E2F4 and E2F5), activate a network of downstream MCC factors including forkhead box J1 (FOXJ1), v-myb avian myeloblastosis viral oncogene homolog (MYB), and cyclin O (CCNO) (Tan et al 2013; Boon et al 2014; Ma et al 2014; Wallmeier et al 2014). Recent studies also showed that TAp73 , a P53 family member that acts downstream of Gemc1 in multiciliogenesis, plays an important role in the MCC program through activation of downstream genes including Foxj1 and Myb (Jackson and Attardi 2016; Marshall et al 2016; Nemajerova et al 2016; Lalioti et al 2019a). Disruption of the GEMC1-MCIDAS network leads to defective multiciliogenesis in different tissues, whereas mutations in both GMNC , the human ortholog of GEMC1 , and MCIDAS have been identified in human ciliopathies (Spassky and Meunier 2017; Lewis and Stracker 2020).…”
Section: Introductionmentioning
confidence: 99%